Natural resources and income inequality in Africa. - Charasz, Pawel. (2014)
This paper hypothesises about natural resources being an important determinant of income inequality in Africa. Using a panel dataset for 53 African countries over the period 1960-2010 I empirically test my prediction and indeed find natural resources to be a significant factor affecting the level of income inequality. However, the overall effect is dependent upon the political regime and level of population heterogeneity. Whereas natural resources themselves were on average contributing positively to income inequality, greater degree of democracy reduces this effect and greater level of population heterogeneity increases this effect.